MUSEUMS ARE CULTURAL AND EDUCATIONAL ORGANIZATIONS - Aytmuratova Hurliman (Journals Park Publishing, 2024)
Establishment of the museums, the tourism of Karakalpakstan Republic and museums’ of such place, the developmental tourism strategy of Karakalpakstan Republic.
Keywords: museion, museyon, the place of Fessaliya, the Louvre of desert, strategy, the picture of “Shelekli a’yel”.